2009
DOI: 10.1164/rccm.200805-741oc
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory Pharyngeal Narrowing during Central Hypocapnic Hypopnea

Abstract: Expiratory pharyngeal narrowing occurs during central hypocapnic hypopnea. Reduced ventilatory drive leads to increased expiratory, but not inspiratory, upper airway resistance. Central hypopneas are obstructive events because they cause pharyngeal narrowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 29 publications
2
46
0
2
Order By: Relevance
“…In one study [13], electromyogram recordings demonstrated that pharyngeal constrictors were inactive, suggesting passive airway closure. In addition, SANKRI-TARBICHI et al [14] and BADR et al [15] observed diminished pharyngeal cross-sectional area on video-endoscopy associated with increased upper airway resistance during induced central hypocapnic hypopnoea. Of note, retropalatal narrowing under these low drive/hypotonic conditions occurred predominantly during the expiratory phase [14].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study [13], electromyogram recordings demonstrated that pharyngeal constrictors were inactive, suggesting passive airway closure. In addition, SANKRI-TARBICHI et al [14] and BADR et al [15] observed diminished pharyngeal cross-sectional area on video-endoscopy associated with increased upper airway resistance during induced central hypocapnic hypopnoea. Of note, retropalatal narrowing under these low drive/hypotonic conditions occurred predominantly during the expiratory phase [14].…”
Section: Discussionmentioning
confidence: 97%
“…Upper airway closure has previously been reported to occur in some forms of both spontaneous and experimentally induced central apnoea [7,[12][13][14][15].…”
mentioning
confidence: 99%
“…c) the airway can close during polysomnographic central apnea; (Badr 1996;Badr et al 1995) d) central hypopneas demonstrate flow-limitation (Badr et al 1995;Sankri-Tarbichi et al 2009;Guilleminault et al 1997;Dowdell et al 1990). Despite the known presence of flow limitation and airway narrowing during both central and obstructive events (Dempsey et al 2014), hypopnea scoring is biased towards obstructive disease (Rao & Thomas 2013;Eckert et al 2007;Javaheri & Dempsey 2013).…”
Section: Accurate Estimation Of Central Sleep Apnea From Clinical Polmentioning
confidence: 99%
“…Narrowing of the pharynx on expiration occurs during central hipocapnic hypopnea, supporting the concept that the presence of flow limitation by itself cannot be used to distinguish between obstructive and central hypopnea. [18][19][20] We consider that scoring central and mixed events in polysomnography is important not only in the baseline assessment of sleep-related breathing disorders, but it should also be taken into account by the criteria used to estimate the therapies success.…”
mentioning
confidence: 99%